(untitled) (Journal of Face Aesthetics, 2023)
At the University Centre for Specialised Medicine Dentistry, a workshop session in collaboration with Beauty Derm Aesthetic and INNMEDIS was held on the second day of the International Scientific and Training Conference "New Possibilities in Oral Therapy in Aspects of Facial Aesthetics" taking place on 22–23.10.2022. All Conference Participants and Students of the 8th edition as well as previous editions of the Postgraduate Course "Facial Aesthetics" at the Poznan University of Medical Sciences, were able to become acquainted with the product portfolios of both companies, as well as carry out facial aesthetic medicine procedures. The first day of the conference was entirely lecture‑based, with lectures covering issues of a broadly holistic approach to facial aesthetics.